Gambaran Resiliensi Individu Penyintas Bencana Alam: Kajian Literatur - Resawan, Made Agus Nanda Ari; Nurcahyo, Firmanto Adi (Universitas Medan Area, 2025)
This study aims to describe the resilience of individual survivors of natural disasters and identify the factors that play a role in shaping their resilience. The method used is a literature review of articles or research reports published in the last 7 years, from 2016-2023. Data collection uses article search techniques on Google Scholar. The number of articles analyzed was 10 articles. Quality assessment is based on journal indexation in Sinta and Garuda. The data synthesis technique used was thematic analysis. The results of this research obtained an overview of the resilience of natural disaster survivors in terms of seven aspects of resilience, namely emotion regulation, impulse control, causal analysis, optimism, empathy, self-efficacy, and reaching out. Of the 10 articles analyzed, four articles discussed these seven aspects of resilience. In this study, the factors that influence the resilience of natural disaster survivors are grouped into two factors, namely internal factors and external factors. Internal factors consist of: (1) social factors; (2) social capital factors, and; (3) economic factors. External factors consist of: (1) institutional factors, and; (2) infrastructure factors. The findings are expected to enrich the literature on disaster psychology and resilience and become the basis for developing psychosocial programs or interventions for natural disaster survivors.